Moving in and out of Islam - Nieuwkerk, Karin van, 1960- (University of Texas Press, 2018)
Embracing a new religion, or leaving one?s faith, usually constitutes a significant milestone in a person?s life. While a number of scholars have examined the reasons why people convert to Islam, few have investigated why people leave the faith and what the consequences are for doing so. Taking a holistic approach to conversion and deconversion, Moving In and Out of Islam explores the experiences of people who have come into the faith along with those who have chosen to leave it?including some individuals who have both moved into and out of Islam over the course of their lives. Sixteen empirical case studies trace the processes of moving in or out of Islam in Western and Central Europe, the United States, Canada, and the Middle East. Going beyond fixed notions of conversion or apostasy, the contributors focus on the ambiguity, doubts, and nonlinear trajectories of both moving in and out of Islam. They show how people shifting in either direction have to learn or unlearn habits and change their styles of clothing, dietary restrictions, and ways of interacting with their communities. They also look at how communities react to both converts to the religion and converts out of it, including controversies over the death penalty for apostates. The contributors cover the political aspects of conversion as well, including debates on radicalization in the era of the "war on terror" and the role of moderate Islam in conversions.